Taking Firms to the Stock Market: IPOs and the Importance of Large Banks in Imperial Germany 1896-1913 - Sibylle H. Lehmann (European Historical Economics Society (EHES), 2012)
Large universal banks played a major role for Germany's industrialisation because they provided loans to the industry and thereby helped firms to overcome liquidity constraints. Previous research has also argued that they were equally important on the German stock market. The present paper provides quantitative and qualitative evidence that although the market for underwriters was dominated by a small oligopoly of six large banks, there was still perceptible competition, which kept fees and short run profits low. Another interesting finding of the paper is the absence of a signalling effect to investors. Neither underpricing nor the one year performance was different for the IPOs issued by one of the Big Six. Thus, although the German IPO business was in the hands of a small oligopoly, investors did not benefit from the lack of competition. One explanation is that the quality of IPOs on the German stock market of the time was very good in general caused by the competition between underwriters, but also by the tight regulation of underwriting, which ensured thequality of all firms on the German stock market.
Keywords: G21; G24; N23; 330; Financial History; Universal Banks; IPOs